Community arts as an inclusive methodology for sustainable tourism development - Yuthasak Chatkaewnapanon (2019)
© 2019, Emerald Publishing Limited. Purpose: Community arts practice gives voice to a younger generation, who must be studied as part of the development process from commencement, to accomplish building sustainable destination development in the direction of future prosperity for the rural community. Design/methodology/approach: This paper challenges a relatively weak critical practice of the community-based tourism (CBT) by introducing community arts methodologies as a research approach in the context of tourism, the opportunity is created to give voice to a younger generation that must also be included in the development aims of the CBT to achieve sustainable community tourism development. Findings: The CBT aims to support access to quality participation in the development process. However, investment in education and building tourism entrepreneurs is not inclusive of the future generations beyond the original generation. Consideration of the desires and imaginations of the future generations must be part of the CBT project for tourism development sustainability. Building awareness of the fragility and value of tourist attractions and resources, in a younger generation that never experienced the original attractions of the traditional village, is critical to achieving the objectives of the CBT. Research limitations/implications: The paper is not yet attempting to examine the empirical data of this research. Rather, it challenges current CBT research processes as having a narrow reach into a community. Practical implications: Tourism developers and local communities should include an understanding of what directions and what opportunities the next and future generations will have to continue sustainable development. Including children’s imaginations into a community’s tourism development plans will benefit awareness of the present context and assist locals in forecasting the next stage of village development. The present tourism planners would then have a holistic vision for a design strategy sustaining rural livelihoods that acknowledge the limits of nature-based resources and cultural resources. Social implications: Community arts research offers the possibility of inclusive participation of community members. Arts methodology attempts to articulate ideas in visual form, for the aim of discussion, reflection and realization of the desires and concerns of the community in terms of lifestyle, environment and cultural heritage, in preparation for the future generation taking control of tourism development. The process aims to impact future decisions effecting the course of tourism development in rural Thailand. Originality/value: The paper discusses the potential contribution of community arts practice as a complementary tool by taking into account different aspects of sustainable tourism into CBT concept. The paper evaluates what has been missing in advancing our understanding of sustainable rural tourism development in Thailand. It fills the gaps with a methodological approach that gives voice to the local community. The purpose of this paper is to rethinking the ideology and approach of CBT to be inclusive of all demographics of society for the goal of achieving sustainable tourism and sustainable community development in Thailand context.